Causes of Infertility amongst Couples Visited at Infertility Centre Kathmandu, Nepal - Neupane, Pratima; Sharma, Deepak; Panta, Prem Prasad; Aryal, Bijay; Poudel, Tarun; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Infertility is being a common global problem affecting one couple in six. Approximately 167 million ever married women aged 15-49 years in developing countries were infertile. The problem of infertility has not given attention considering the fact that it is not the life threatening, but, it has substantial community health problems such as depression, anxiety domestic violence and social isolation. The purpose of the study was to explore the causes of infertility among couples who visited the infertility centre. Methodology: Hospital based descriptive cross-sectional study had been carried out in infertility centre Kathmandu Nepal. One hundred and sixty five married couple with infertility problem availing the infertility treatment was selected on first come first serve basic sampling method from infertility treatment centre. Result: The infertility problem varied with the age. The problem was highest among the females of age group 26-30 years (51%), similarly in males it was predominant at the age of 31-35 years (45%). The most common causes of female infertility were ovarian cyst (37%) and heavy bleeding (18.7%), uterine fibroids (9%), Pelvic inflammation (9%), Thyroid disease (21.8%), whereas in males the infertility were mostly due to Oligospermia (17.5%), Azoospermia (5.5%), Hydrocele (7.8), Mumps orchids (6%). Conclusion: Infertility was due to various causes in the male or/and the female partner, however, the infertility among couples were mostly due to the problem in females. Infertility is a complex problem that should be considered carefully by the individual, community peoples, government and stakeholders in each country.